Analisis Komunikasi pada Aplikasi MiChat sebagai Sarana Media Prostitusi Online di Pontianak - Zakaria Efendi (LP2M UIN Sunan Kalijaga, 2021)
Nearly all of social media provide a GPS feature that allows users to find each other around them. One of them is MiChat. In Pontianak this application is one of the social media that is widely misused as a means of communication for online prostitution. This study is trying identify and describe the communication process tha is occured in the MiChat application, as a means of online prostitution, and figure out some cases of online prostitution in Pontianak using MiChat. This study draw upon communication analysis and descriptive qualitative methods by collecting data that are obtained by interviews, observations, and literature exploration from online and print news. Furthermore, the supporting data comes from books and scientific articles. The results of the study indicate the fact that being a prostitute is considered a promising job for the perpetrators because they can earn money easily. Economic and lifestyle factors are the reasons behind the perpetrators to become prostitutes. Many sex workers are turn out to be underage and not only from the area around Pontianak but also comes from Java, Sumatra, Sulawesi and other country. Running MiChat application for prostitution transactions is only a negative use of social media, because of its privation that is considered more secure. The conclusion of this research is that serious action is necessary from the regional and central governments to review the operational permits of social media that consist of potential to be used as a means of online prostitution. Law enforcers must seriously monitor and regulate prostitution activities in Pontianak which are carried out via offline and online. Serious attention is necessary for parents to children. Moral cultivating and character education needs to be considered since an early age so that children grow up with strong religious provisions so they don't fall into promiscuity and prostitution.[Hampir semua media sosial menyediakan fitur GPS yang dapat mempertemuka penggunanya dengan pengguna lain disekitarnya. Salah satunya adalah MiChat. Di Pontianak aplikasi ini menjadi salah satu aplikasi chatting yang banyak disalahgunakan sebagai sarana komunikasi prostitusi online. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan proses komunikasi yang digunakan dalam aplikasi MiChat, penyalahgunaan MiChat sebagai sarana prostitusi online, dan kasus prostitusi online di Pontianak menggunakan MiChat. Penelitian ini menggunakan analisis komunikasi dan metode kualitatif deskriptif dengan mengumpulkan data melalui wawancara, observasi, dan eksplorasi literatur dari berita online maupun cetak. Data pendukung berasal dari buku dan artikel ilmiah. Hasil penelitian menunjukkan fakta bahwa menjadi PSK dianggap menjadi pekerjaan yang menjanjikan bagi para pelaku karena dapat memperoleh uang dengan mudah. Faktor ekonomi dan gaya hidup melatarbelakangi para pelaku untuk menjadi PSK. Banyak ditemukan, para PSK masih di bawah umur dan tidak hanya berasal dari daerah sekitar Pontianak melainkan juga berasal dari Jawa, Sumatera, Sulawesi dan daerah lain. Penggunaan aplikasi MiChat untuk prostitusi merupakan sebuah pemanfaatan media sosial secara negatif, karena keamanan aplikasi ini dinilai lebih terjamin. Oleh karenanya, perlu tindakan serius dari pemerintah daerah dan pusat untuk meninjau kembali izin operasional media sosial yang berpotensi digunakan sebagai sarana prostitusi online. Penegak hukum harus serius memantau dan menertibkan kegiatan prostitusi di Pontianak yang dilakukan via offline maupun online. Perlu perhatian serius dari orangtua kepada anak-anak. Pendidikan akhlakul karimah dan pendidikan karakter perlu ditanamkan sejak dini agar anak-anak tumbuh dengan bekal agama yang baik agar tidak terjerumus pada pergaulan bebas dan prostitusi.]